Predicting the Desire for Remarriage Based on Family Relationships, Attachment Styles, and Personality Traits Among Married Men - Araghchi , Elham; Saadati, Nadereh (KMAN Counseling & Psychology Nexus, 2023)
The present study aimed to investigate the multifaceted relationships between family relationships, attachment styles, and personality traits with the desire for remarriage among married men in Isfahan. The research method was descriptive and correlational. The statistical population consisted of all married men in Isfahan during the years 2016-2017. The sample included 195 married men selected through convenience sampling. The research instruments were the Remarriage Desire Scale, the Family Relationships Questionnaire (Olson & Barnes, 2004), the Attachment Styles Questionnaire (Armsden & Greenberg, 1987), and the NEO Five-Factor Personality Inventory (Costa & McCrae, 1997). Data were analyzed using both descriptive statistics (mean and standard deviation) and inferential statistics (Pearson correlation and stepwise regression analysis). Analyses were conducted using the SPSS statistical package. Results showed that the predictor variables of family relationships, insecure attachment style with father, neuroticism, agreeableness, and conscientiousness significantly related to the desire for remarriage among married men, with family relationships having predictive power for the desire for remarriage in married men. Based on these results, it can be said that an increase in the experience of satisfactory family relationships, conscientiousness, and agreeableness reduces men’s desire for remarriage, while neuroticism and insecure attachment style with father increase the desire for remarriage in these men. Additionally, satisfactory family relationships can predict a decrease in the desire for remarriage among married men. Thus, if women can form a good relationship with men, they can reduce their husbands’ desire for remarriage.